Nilai Pendidikan Karakter Dalam Novel Pulang Pergi Karya Tere Liye - Harahap, Zillingjy; Rahayu, Sri (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Character education is very important in education, with character education, students can build  personalities as people with good character and noble morals. There are several ways to build students character, one of which is by reading novels. In novels character education values are often found. Therefore, researchers want to know and discuss the character education values that can be found in the novel Pulang Pergi by Tere Liye. The character education values that will be studied in the novel are categorized into 18 aspects, namely: (1) religious, (2) honest, (3) friendly/communicative, (4) peace-loving, (5) tolerance, (6) discipline, (7) fond of reading, (8) caring for the environment, (9) hard work, (10) creative, (11) independent, (12) democracy, (13) curiosity, (14) national spirit, (15) social care, (16) responsibility, (17) love of the homeland, and (18) appreciating achievement. The purpose of this study is to describe, analyze, and interpret the character education values that have been found in the novel Pulang Pergi by Tere Liye. The formulation of the problem in this study is: (1). What are the character education values contained in the novel Pulang Pergi by Tere Liye? This study uses a descriptive analytical method, so that the results of the study can be presented systematically, descriptively and in detail, then processed and analyzed to draw conclusions. The data collection technique used is the hermeneutic technique which is a reading, recording and concluding technique. The number of data found was 359 data. The results of the study indicate that the value of character education in the novel Pulang Pergi by Tere Liye has more friendly/communicative character education values with 64 data analyzed and fewer character education values of love for the homeland which only have 2 data analyzed